Characterization of Follicular Lymphoma in the Small Intestine Using Double-Balloon Endoscopy - Manzurul Chowdhury; Masaki Endo; Toshimi Chiba; Norihiko Kudara; Shuhei Oana; Kunihiko Sato; Risaburo Akasaka; Kazumitsu Tomita; Saori Fujiwara; Tomomi Mizutani; Tamotsu Sugai; Yasuhiro Takikawa; et al. (Gastroenterology Research and Practice)
Follicular lymphomas occur rarely in the gastrointestinal tract, representing only 1–3% of all gastrointestinal tract B-cell non-Hodgkin lymphomas. We describe endoscopic analysis of 3 cases of follicular lymphoma in the small intestine using double-balloon endoscopy. Double-balloon endoscopy revealed multiple nodular lesions and elevated white patches, multiple polypoid lesions, and scattered white polypoid and nodular lesions in the duodenum and small intestine. Fuji Intelligent Chromo Endoscopy demonstrated small, whitish nodules, and narrow-band imaging showed a coiled, elongated vascular pattern within the elevated lesions. These cases are the first follicular lymphomas in the small intestine evaluated using narrow-band imaging or Fuji Intelligent Chromo Endoscopy to be reported.